Cultures and organizations : software of the mind : intercultural cooperation and its importance for survival - Hofstede, Geert H; Hofstede, Gert Jan; Minkov, Michael (New York : McGraw-Hill, 2010)
The revolutionary study of how the place where wegrew up shapes the way we think, feel, and act--with new dimensions and perspectives Based on research conducted in more than seventy countries over a forty-year span, Cultures and Organizations examines what drives people apart-when cooperationis so clearly in everyone's interest. With major new contributions from MichaelMinkov's analysis of data from the World Values Survey, as well as an account ofthe evolution of cultures by Gert Jan Hofstede, this revised and expanded edition: Reveals the "moral circles" from which national societiesare built and the unexamined rules by which people think, feel, and act Explores how national cultures differ in the areas of inequality, assertiveness versus modesty, and tolerance for ambiguity Explains how organizational cultures differ from nationalcultures-and how they can be managed Analyzes stereotyping, differences in language, cultural rootsof the 2008 economic crisis, and other intercultural dynamics.-- Provided by publisher
-- part leaves The concept of culture. The rules of the social game -- Studying cultural differences -- part ll. Dimensions of national cultures. More equal than others -- I, we, and they -- He, she, and (s)he -- What is different is dangerous -- Yesterday, now or later? -- Light or dark? -- part lll. Cultures in organizations. Pyramids, machines, markets, and families: organizing across nations -- The elephant and the stork: organizational cultures -- part lV. Implications. Intercultural encounters -- The evolution of cultures
Includes bibliographical references and indexes
Keywords: Intercultural communication; Organization -- Research; International cooperation; National characteristics; Ethnopsychology; Cultural pluralism